Spatial Spillover Effects Promote the Overall Improvement of Urban Competitiveness: Evidence of SDM in Asian Cities - Liu, Cheyuan; Peng, Michael Yao-Ping; Gong, Weijin (Frontiers in Environmental Science, 2022)
With the continuing rise of the economies of China, India and other developing countries and the continuous eastward movement of the global economic center, it is necessary for Asia to improve its overall competitiveness, as it has become the focus of the world economy since the economic crisis. This study uses the latest spatial econometrics technique to explore the influencing factors and spatial spillover effects of the economic competitiveness of 565 cities in Asia. The study finds that the factor spillover bandwidth affecting the improvement of urban competitiveness is primarily concentrated in the range of 1000 km. Furthermore, with a maximum elasticity value of roughly 11.6 %, a city's spatial spillover effect is a crucial factor in selecting strategies for enhancing its competitiveness level. Financial services, industrial structure, and human resources all have an influence on the level of urban competitiveness. The empirical outcomes of this study have a high reference value for enhancing the competitiveness of target cities, developing urban agglomerations, and evaluating the hinterland of economic belts.